Preference in Girls’ Lower Limb Tasks: 女童對下肢動作的偏向 - NONIS, Karen P.; LARKIN, Dawne; PARKER, Helen E. (Asian Journal of Physical Education & Recreation, 2006)
LANGUAGE NOTE | Document text in English; abstract also in Chinese. The research on laterality indicates that children become increasingly right preferent with age but these relate mainly to data on the upper limbs while lower limb preference is limited. This study investigated the direction of six lower limb preference tasks which included: kicking (stationary and moving ball); pick-up; step-up; balance and hopping. Fifty-one girls in the age group of 3, 4, 5 and 6 years were tested over four sessions at four monthly intervals and classified as right, left or mixed preferent after performing on two successive trials. This study hypothesized that girls would become increasingly right preferent with age and that lower limb preference would differ for each task. Data analysis used a three-way ANOVA repeated measures procedure with Age (4 levels) as the between subjects factor and Session (4 sessions) and Task (6 tasks) as the within subjects factors (N = 51). The ANOVA results showed two task groupings indicating that lower limb preference is task dependent. The authors proposed the interaction of individual differences, changing task and environmental demands influence the expression of lower limb preference. 偏向的研究顯示孩童随著年齡的增長會逐漸向右邊偏向，但這些卻主要是針對上肢的研究資料，而對下肢偏向的資料卻有限。本報吿探討六種下肢偏向的動作方向測試，其中包括：踢腿(定點和滾球)、拾起、踩踏、平衡和定點彈跳。五十一位三至六歲的女童參與四次測試，每次測試相隔四個月。在連續兩次嘗試後，將她們分類為向右偏向、向左偏向和綜合偏向。這項研究假設女童隨著年齡的增長，會逐漸有向右邊的偏向，對下肢的偏向會隨著動作的不同而有所改變。報告的資料分析使用了三項ANOVA反復測量規程，以年齡(4個數值)作為物件之間的因素，測試(4次測試)和動作(6個動作)作為物件之內的因素(N = 51)。ANOVA的 結果呈現兩種動作類，顯示對於下肢的偏向是取決於動作的。作者提出看法，認為各個不同孩童的互動、動作和環境的轉換都對下肢偏向起著影響。